PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT KERTA MULYA SEJAHTERA DI RUMPIN BOGOR - Safiih, Abdul Rahman; Waliyudin, Arif (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the effect of competency variables on employee performance, to determine the effect of work discipline variables on employee performance and to determine the effect of competency variables and work discipline simultaneously on employees performance at PT. Kerta Mulya Sejahtera. The research method used was quatitative involving 61 employees as samples using saturated sampling techniques. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t test and f test. The results showed that: (1) competence affects employee performance at PT. Kerta Mulya Sejahtera, this can be proven from the simple linear regression equation Y = 32.577 + 0.233X1 and the calculated value of 2.141 > table 2.00172 with a significant of 0.000 < 0.05. (2) Work Discipline affects employee performance at PT. Kerta Mulya Sejahtera, this can be proven from the simple linear regression equation Y = 18.279 + 0.555X2 and the calculated value of 4.018 > table 2.00172 with a significance of 0.000 < 0.05. (3) Simultaneously there is an influence between competence and work discipline on employee performance at PT. Kerta Mulya Sejahtera, this can be proven from the multiple linear regression equation Y = 12.306 + 0.184X1 + 0.516X2, the correlation value is 0.538, the value of the coefficient of determination is 29.0%, and the calculation value is 11.821 > table 3.16 with a significant level of 0.000 < 0.05.